1981
DOI: 10.1258/002367781780959107
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine alone and combined with diazepam or xylazine in laboratory animals: a 10 year experience

Abstract: 163Summary Ketamine alone or supplemented by diazepam or xylazine has been used and evaluated as an anaesthetic in a range of animals including snakes,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
187
2
10

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(211 citation statements)
references
References 13 publications
12
187
2
10
Order By: Relevance
“…When used appropriately, these medications induce a desirable state of calm or sedation (Vesal et al 2011). Ketamine and xylazine were selected because they achieved rapid and deep sedation which was reported to be more effective in several animal species (Green et al 1981). This study demonstrated that the combination of ketamine and xylazine was effective and safe for intravenous induction.…”
Section: Discussionmentioning
confidence: 99%
“…When used appropriately, these medications induce a desirable state of calm or sedation (Vesal et al 2011). Ketamine and xylazine were selected because they achieved rapid and deep sedation which was reported to be more effective in several animal species (Green et al 1981). This study demonstrated that the combination of ketamine and xylazine was effective and safe for intravenous induction.…”
Section: Discussionmentioning
confidence: 99%
“…Glenn et al (1972) determinaram a DL 50 da cetamina para serpentes da espécie Crotalus atrox como 154mg/kg e que doses entre 55-88mg/kg promoveram uma contenção química adequada para a realização de pequenos procedimentos. Outros artigos também citam doses entre 50-80mg/kg como adequadas para contenção (Cooper 1974, Green et al 1981, Hill & Mackessy 1997 com período de latência de até 30 min. Destaca-se que como os agentes dissociativos promovem discreta analgesia visceral (Bennett 1991), o uso de cetamina isolada deve ser realizado apenas para contenção física ou procedimentos cirúrgicos cutâneos.…”
Section: Discussionunclassified
“…O uso isolado da cetamina é realizado há vários anos em serpentes para facilitar a contenção, possibilitar a realização de exames clínicos e diminuir o estresse do procedimento (Glen et al 1972, Cooper 1974, Hill & Mackessy 1997. Entretanto, poucos enfatizam as alterações fisiológicas dos animais no período trans-anestésico, atentando-se apenas na possibilidade de contenção e a segurança do procedimento, tanto para o animal quanto para o profissional (Green et al 1981, Schumacher et al 1997.…”
Section: Introductionunclassified
“…The compounds used in this study induced pulmonary disease with differing histopathologic features that became less distinctive by post-inoculation day 7 depending on the compound instilled. We conclude that energy dispersive spectroscopy is a useful diagnostic adjunct for detection and confirmatory identification of the specific elemental composition of certain foreign materials in lungs.…”
Section: Discussionmentioning
confidence: 99%